Estudo das características físico-químicas do solo em plantio de erva-mate (Ilex paraguariensis St. Hil.) através da geoestatística e do geoprocessamento - Silva, Carlos Roberto Santos da (2007)
This work was based in methods of classic descriptive statistics, methods of geostatistics and geoprocessing, in the identification of the size and the structure of the spatial variability of the physical and chemical attributes of the soil in area of Paraguay Tea forestry. The area of study, localized in the Tupian Farm, in the municipality of New Silver, RS, where were raised samples from January to March, 2005, embracing the Latosoil humic dystrophic soil. It was accomplished systematic sample with grid of regular spacing among the one hundred meter points, totalizing thirty-six sample points and the six hundred and thirty pairs of data, in an area of thirty-six hectares. Were collected samples of soil in situ for analysis in laboratory of the physic attributes of the bulky sand (BS), thin sand (TS) , silt (SIL), argil (ARG), soil density (SD), particle density (PD) and whole porosity (WP) and chemical attributes of argil, texture, pH (H2O), phosphorus (P), potassium(P), organic material (OM), aluminum (AL), calcium (Ca), magnesium (Mg), exchangeable aluminum (H + Al), cations real exchange capacity (CTCe), cations exchange capacity to pH7 (CTCpH7) and saturation of basis (V%). The magnitudes of spatial variabilities were obtained by the variation of coefficient (CV%), with confidence level of 95%, through Microsoft Office Excel 2003 program, while the structure was identified by semivariogrames, in applications geostatistics establishing the necessary parameters to the krigagem . All models of semivariogrames presented zones of anisotropic influence, having its spatial variability the greatest in the perpendicular sense to these areas the declivity. The chemical attribute that presented greatest variability was phosphorus (P), with CV%=127,73, followed by the aluminum attribute (Al), com CV%= 99,23 and the attribute of least variability was the pH (H2O), com CV%=0,0013. To the physical attributes in the distribution of particles size (%), the attribute of greatest variability was bulky sand, with CV%=36,39, while the statistics made to the density attributes of soil, what present the greatest variability was the attribute of whole porosity, with CV%=95,49 and they least variability was verified was the argil, with CV%=12,32. IN the analysis of the structure of the spatial variability through geostatistics, the chemical attribute Ca presented IDE (%)=64,42 and the physical attribute ARG with IDE (%)=62,50, getting the greatest rates. To the accomplishment of agreement in the program VARIOWIN® 2.21- Software for Spatial Data Analysis , the method used was the visual, named the feeling , where the Spherical model was what better was adapted to the studied attributes, indicated in 55% of the variogrames. The Gaussian s model to the attribute of texture got the most overtaking with a (m)=421. A crusade validation with the usage of the program GSLIB90 Geostatistical Software Library pointed out accuracy in the agreement of the variographic models, having the attributes Ca, Al and ARG with R² (%) of 0,841; 0,705 and 0,760, respectively. The usual krigagem of the studied attributes permitted the detailed of the distribution of these through the maps of isolineas.